Uji Aktivitas Antibakteri dan Antibiofilm Minyak Atsiri Rimpang Bengle (Zingiber purpureum Roscoe) terhadap Bakteri Staphylococcus epidermidis (Antibacterial and Antibiofilm Activity Test of Bengle Rhizome Essential Oil (Zingiber purpureum Roscoe) agains - Hidayatul Ulyah; Evi Umayah Ulfa; Endah Puspitasari (UPT Percetakan dan Penerbitan Universitas Jember, 2015)
Staphylococcus epidermidis has become one of the most important pathogenic bacteria that lead to nosocomial infection. This is caused by its ability to form a biofilm on the surface. Essential oils are one of the natural product that could be used as antiinfection agents. Bengle rhizome essential oil has been known to have activity against non-pathogenic bacteria S. epidermidis. This study was proposed to know the antibacterial and antibiofilm activity of bengle rhizome essential oil against clinical isolate of S. epidermidis at concentrations of 45, 60, 75, and 90%. Antibacterial activity was determined by the diffusion method with hole plate technique, while antibiofilm activity was determined by the microtiter assay method with crystal violet staining and quantified by measuring the optical density (OD) at λ 595 nm. This study showed that bengle rhizome essential oil has antibacterial and antibiofilm activity. The largest antibacterial and antibiofilm activity was shown from 90% concentration of bengle rhizome essential oil. Keywords: nosocomial infections, antibacterial, antibiofilm, bengle essential oil, Staphylococcus epidermidis.